2019
DOI: 10.1002/jemt.23376
|View full text |Cite
|
Sign up to set email alerts
|

Precision brackets for upper lateral incisors in Bioprogressive therapy

Abstract: Orthodontic brackets, specifically in their slots, are responsible for receiving active orthodontic forces and transferring them to the teeth to be moved. The presence of an altered slot or inaccurate dimensions can influence the mechanical relationship between the bracket and archwire, interfering with the biomechanics of tooth movement. The objective of this study was by comparing the accuracy of slot placement of upper right lateral incisor metal brackets for Bioprogressive Ricketts therapy from five tradem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…The results of this present study are not in accordance with the studies conducted by Rajashekar K et al (2017) 3 , Araujo AVP et al (2019) 16 , Daga et al (2017) 17 , Park JS et al (2020) 18 and Tepedino et al (2020) 19 . Rajashekar K et al 3 found that 50% of brackets were larger and the remaining 50% were smaller than the stated dimension and all brackets were statistically significant (p≤0.05).…”
Section: Discussioncontrasting
confidence: 97%
“…The results of this present study are not in accordance with the studies conducted by Rajashekar K et al (2017) 3 , Araujo AVP et al (2019) 16 , Daga et al (2017) 17 , Park JS et al (2020) 18 and Tepedino et al (2020) 19 . Rajashekar K et al 3 found that 50% of brackets were larger and the remaining 50% were smaller than the stated dimension and all brackets were statistically significant (p≤0.05).…”
Section: Discussioncontrasting
confidence: 97%
“…unit standardization; they are among the researchers who have defined the spectrum of slot and archwire manufacturing features. [ 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 ]…”
Section: Introductionmentioning
confidence: 99%
“…These comprise leaf gauges, pin gauges, digital gauges, a profile projector microscope, a stereomicroscope, an optical microscope, a scanning electron microscope, and a micro-CT scanner. [ 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 ]…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the parallelism of the inner wall of the slot, Major et al [24] measured the manufacturing tolerance of the orthodontic bracket slot and reported a convergent taper of 1.47°, a slightly divergent taper below that, and the most rectangle in shape depending on the product. Araujo et al [25] reported that there was no significant difference in torque manufacturing tolerance, and that it converged with respect to the parallelism of the inner wall of the bracket slot, and that the average parallelism was measured from +0.19 to -4.10 depending on the manufacturer [11,26,27]. In this study, the slot base angle was the same as the torque of the bracket prescription, and in order to check the tolerance according to the manufacturer, the torque and parallelism of the actual bracket were measured with a scanning electron microscope, and it was confirmed that it was within the manufacturing error.…”
Section: Discussionmentioning
confidence: 99%